Synthesis of single crystal α-Fe2O3 nanotube via facile route and discussion of formation mechanism - Tai, Y. P. (2013)
Single crystal α-Fe2O3 nanotube was synthesised via refluxing in the organic solvent of n-butylalcohol that employed Fe(OH)3 sol as precursor without any surfactant and dispersant. Then the final products were characterised by X-ray diffraction (XRD), energy dispersive X-ray analysis (EDAX), transmission electron microscopy (TEM) and UV-Vis absorption spectroscopy. The XRD analysis confirmed trigonal crystal system α-Fe2O3 with high purity and good crystallinity, which were confirmed further by EDAX pattern. The TEM images displayed the morphology of α-Fe2O3 which was mainly nanotubes with outer diameters of 10‐15 nm, inner diameters of 6‐10 nm and length of 100‐120 nm. The poly vinyl alcohol (PVA)‐α-Fe2O3 nanocomposite obtained by doping the product in PVA showed a strong absorption both in UV and visible regions. Furthermore, the possible formation mechanism was proposed based on the experimental results, which revealed that the nanotubes were easily obtained in the interface of collide and n-butyl alcohol by the surface tension.